Crystallization and preliminary x-ray characterization of a lectin from Cicer arietinum (chickpea) - Katre, Uma V.; Gaikwad, S. M.; Bhagyawant, S. S.; Deshpande, U. D.; Khan, Mohammad Islam; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2005)

Convergent approach toward the synthesis of the stereoisomers of C-6 homologues of 1-deoxynojirimycin and their analogues: evaluation as specific glycosidase inhibitors - Pandey, Ganesh; Dumbre, Shrinivas G.; Khan, Mohammad Islam; Shabab, M. (Journal of Organic Chemistry, 2006)
A new and stereoselective strategy is developed to synthesize an appropriate template 9 to obtain C-6 homologues of 1-deoxyazasugars such as 1-deoxy-D-galactohomonojirimycin ( 5), 1-deoxy-4-hydroxymethyl-D-glucohomonojirimycin (6), and their enantiomers. The template 9 is also used to obtain neutral nonbasic pseudo-glyconolactam (8), C-4 amino, and methyl analogues of 1-deoxy- homonojirimycin as new analogues of 1- deoxyhomoazasugars. Compound 5 is found to be a potent and specific inhibitor to alpha-galactosidase (K-i = 1.7 mu M). Similarly compounds 6 (K-i = 28 mu M), ent-5 (K-i = 129 mu M), and ent-6 K-i = 12 mu M) exhibited specific inhibition of beta-glucosidase.

CdS quantum dots: enzyme mediated in vitro synthesis, characterization and conjugation with plant lectins - Ansary, Abu Ayoobul; Kumar, S. Anil; Krishnasastry, M. V.; Abyaneh, Majid Kazemian; Kulkarni, Sulabha K.; Ahmad, Absar; Khan, Mohammad Islam (Journal of Biomedical Nanotechnology, 2007)
This paper presents the in vitro synthesis of CdS quantum dot nanoparticles using sulphite reductase and capping peptide in the presence of a co-factor alpha-NADPH, their characterization and conjugation with plant lectins, Jacalin and Chick pea lectin. Incubation of sulphite reductase with aqueous CdCl2, Na2SO3, and capping peptide in the presence of a-NADPH, which acts as a co-factor, resulted in the formation of CdS nanoparticles of dimensions 5-20 nm. These CdS nanoparticles were conjugated with plant lectins by EDAC mediated coupling. These observations are of significance, as it will help in the development of eco-friendly process for the formation of CdS nanoparticles and their application as fluorescent biolabels. Moreover the above studies will also help in designing a rational enzymatic strategy for the synthesis of nanomaterials of different chemical composition, shapes and sizes as well as their separation.
Keywords: bio-label; CdS quantum dots; conjugation; Enzyme; in vitro synthesis; Nanoparticles

Chemical, thermal and pH-induced equilibrium unfolding studies of fusarium solani lectin - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The effect of urea, guanidine thiocyanate, temperature and pH was studied on the conformational stability of Fusarium solani lectin. Equilibrium unfolding with chemical denaturants showed that the lectin was least stable at pH 12 and maximally stable at pH 8.0 near its pI ( 8.7). Guanidine thiocyanate ( the concentration of denaturant at which the protein is half folded, D-1/2 = 0.49 M at pH 12) was found to be an eight times stronger denaturant than urea (D-1/2 = 3.88 M at pH 12). The unfolding curves obtained with fluorescence and CD measurements showed good agreement indicating a monophasic nature of unfolding and excluded the possibility of formation of any stable intermediate. The effect of pH on the lectin was found to be unusual as at acidic pH, the lectin showed a flexible tertiary structure with pronounced secondary structure, and retained its hemagglutinating activity. On the other hand, the lectin did not show any loss of conformation or activity upto 70 degrees C for 15 min. Moreover, thermal denaturation did not result in the aggregation or precipitation of the protein even at high temperatures. Thermal denaturation was also carried out in the presence of a low concentration of guanidine thiocyanate. Change in the enthalpy of transition (Delta H-m) varied linearly with transition temperature (T-m), which indicated that the heat capacity (Delta C-p =3.95 kJ (.) mol(-1) (.) K-1) of the lectin remained constant during the unfolding.
Keywords: Denaturation; Fusarium solani; guanidine; Lectin; thermal; Unfolding

Complex carbohydrate specificity of lectin from fruiting body of ganoderma lucidum. a surface plasmon resonance study - Thakur, Atul; Pal, Lakhan; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The thermodynamics and kinetics of binding of glycans and glycoproteins to Ganoderma lucidum lectin was studied using surface plasmon resonance. The lectin showed highest affinity for asialo triantennary N glycan (Ka = 3.52 x 10(5)) among the glycans tested. There was a several fold increase in affinity for glycoproteins compared to their corresponding glycans and coincident increase in contribution from enthalpy (Delta H), suggesting the involvement of hydrogen bonding in the interaction as well as involvement of protein-protein interactions. Increased affinity also showed increase in unfavorable negative binding entropy (Delta S) which was compensated with higher enthalpy. The glycoproteins showed faster association rates (k(1)) and the activation energy (E-1(double dagger)) in the association process was much lower for the glycoproteins than glycans, resulting in their faster associations. These observations elaborate the role of protein matrix in lectin-glycoconjugate interaction.
Keywords: ganoderma lucidum; glycans; Lectin; SPR

Click chemistry based rapid one-pot synthesis and evaluation for protease inhibition of new tetracyclic triazole fused benzodiazepine derivatives - Mohapatra, Debendra K.; Maity, Pradip K.; Shabab, M.; Khan, Mohammad Islam (Bioorganic & Medicinal Chemistry Letters, 2009)
We describe herein a one-pot synthesis of novel tetracyclic scaffolds that incorporate a fusion of a proline, 1,2,3-triazole ring with [1,4]-benzodiazepin-8(4H)-one ring systems following click chemistry. The expected peptide bond formation followed by in situ 1,3-dipolar cycloaddition in absence of any catalyst led to the formation of new triazole fused benzodiazepine derivatives. (C) 2009 Published by Elsevier Ltd.

Comparative studies of two araceous lectins by steady state and time-resolved fluorescence and CD spectroscopy - Dharker, Poorva N.; Gaikwad, Sushama M.; Suresh, C. G.; Dhuna, Vikram; Khan, Mohammad Islam; Singh, Jatinder; Kamboj, Sukhdev Singh (Journal of Fluorescence, 2009)
Transitions in the tryptophan microenvironment and secondary structure of two monocot lectins from Sauromatum guttatum and Arisaema tortuosum under different denaturing conditions were studied by steady state and time resolved fluorescence and CD spectroscopy. The lectins exist as tetramers with a single tryptophan residue estimated per monomer, present in a polar environment. Quenching with ionic quenchers showed predominantly electropositive environment for tryptophan residues. Acrylamide had maximum quenching effect. A decrease in KI quenching due to lectin denaturation indicated redistribution of charges as a result of possible conformational change. The two values for lifetimes of tryptophanyl population (1.2-1.4 and 6.3-6.4 ns) reduced substantially on quenching or denaturation. Similarly, both the lectins showed a drastic loss of secondary structure in 5 M Gdn-HCl or 6 M Urea or at pH 2.0 and below. For the first time araceous lectins, like legume lectins are shown to bind adenine. The presence of a compact structure at alkaline pH 10.0-12.0 was observed in CD spectra.
Keywords: Araceae lectins; Denaturation; fluorescence; Lifetime spectroscopy; Secondary structure

Carbon nanotube-modified sodium dodecyl sulfate-polyacrylamide gel electrophoresis for molecular weight determination of proteins - Parthasarathy, Meera; Debgupta, Joyashish; Kakade, Bhalchandra A.; Ansary, Abu Ayoobul; Khan, Mohammad Islam; Pillai, Vijayamohanan K. (Analytical Biochemistry, 2011)
The effect of incorporating carbon nanotubes (CNTs) in the gel matrix on the electrophoretic mobility of proteins based on their molecular weight differences was investigated using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). More specifically, a reduction in standard deviation in the molecular weight calibration plots by 55% in the case of multiwalled carbon nanotubes (MWCNTs) and by 34% in the case of single-walled carbon nanotubes (SWCNTs) compared with that of pristine polyacrylamide gels was achieved after incorporating an insignificant amount of functionalized CNTs into the gel matrix. A mechanism based on a more uniform pore size distribution in CNT modified polyacrylamide gel matrix is proposed. Furthermore, the impact of SWCNTs and MWCNTs on the mobility of proteins in different molecular weight regimes at a given acrylamide concentration offers a tunable gel matrix in terms of the selection of molecular weight ranges of proteins. The robustness and excellent reproducibility of the CNT-PAGE protocol are expected to have a significant impact on the molecular weight determination of newly isolated proteins. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Carbon nanotubes; Gel electrophoresis; Molecular weight determination; Polyacrylamide; Protein separation